(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article examines the enhancement of concrete waterproofing properties by surface impregnation. The relevance of the topic is determined by the high vulnerability of concrete and reinforced-concrete structures to water penetration, capillary suction, corrosion processes, freeze–thaw deterioration and leaching of hydration products. The purpose of the study is to assess the effectiveness of impregnating compositions in reducing permeability and improving the durability indicators of hardened concrete. The paper systematizes the mechanisms of moisture transfer in concrete, characterizes the main types of impregnating materials, and presents a comparative experimental assessment of untreated specimens and specimens treated with sodium-silicate and organosilicon compounds. The results show that impregnation significantly reduces water absorption and capillary moisture uptake and increases water impermeability; at the same time, silicate treatment also provides moderate strengthening of the surface layer. It is substantiated that the impregnation method is an effective technological solution for preventive protection and rehabilitation of concrete structures operated under humid and aggressive environmental conditions.